ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PASIEN POLIKLINIK MATA PADA INSTALASI RAWAT JALAN RSUD. dr. TENGKU MANSYUR KOTA TANJUNG BALAI - Bahtera Bin Purba; Armanda Prima; Afrilius Simanjuntak (Jurnal Penelitian Kesmasy, 2021)
Analysis of Factors Affecting Patient Satisfaction Eye Polyclinic Outpatient Hospital dr. Tengku Mansyur, Tanjungbalai City in 2020. Thesis, Department of Public Health, Faculty of Public Health, Deli Husada Deli Tua Health Institute. This study aims to analyze the relationship between patient satisfaction based on responsiveness, assurance, reliability, empathy and tangiable variables with the quality of service in the eye polyclinic, outpatient installation of dr. Tengku Mansyur, Tanjungbalai City. The population of this study were the patients of the Eye Polyclinic, Outpatient Installation of RSUD dr. Tengku Mansyur, Tanjungbalai City as many as 253 respondents. The method used in this study was analyzed by means of the Chi-Square correlation test. The results of the research on the responsiveness variable showed that the level of responsiveness of Human Resources was 99.6%. For the assurance variable obtained 98.0%. For the reliability variable obtained 98.0%. For the empathy variable, it was obtained 93.7%. For the tangiable variable, it was obtained 90.5%. Based on research conducted from all variables, the service results are very good with a satisfaction level of 88.9%. So it can be concluded that there is a relationship between the variable responsiveness, assurance, reliability, empathy and tangiability with patient satisfaction in the Eye Polyclinic Outpatient Hospital dr. Tengku Mansyur, Tanjungbalai City in 2020.